Perancangan Sistem Pendingin Photovoltaic dengan Memanfaatkan Kontroler Water Spray - abdullah - alhaddad; Muhammad Abdurrahman Hafidhuddien; Ant Ardath Kristi; Noviadi Arief Rachman; Bambang - Susanto; Agus - Risdiyanto; Agus - Junaedi (ELKHA : Jurnal Teknik Elektro, 2020)
Temperature is one of the parameters other than radiation that can affect the performance of photovoltaic (PV) in relation to the output power and efficiency. This paper discusses the design of the PV cooling system using waters pray that controlled automatically. The temperature of the PV on the sensor as input to the controller and the output is the switch settings to turn on/off the pump in spraying water to the surface of the PV panel with the intention that the PV is always maintained at normal temperatures. The system was tested simultaneously on 4 PV panels @ 100Wp by involving PV without a cooling system with the same capacity during the day and the result was compared. Based on the results of PV temperature measurements in relation to the output power shows that PV with a cooling system generates higher output power than PV without a cooling system. By taking into account the involvement of power consumed by the cooling system consists of a controller and pump, the efficiency of PV rises slightly to 1.07 times.